Hexa‐band planar antenna with asymmetric fork‐shaped radiators for multiband and broadband communication applications. Issue 5 (1st April 2016) - Alibakhshi‐Kenari, Mohammad; Naser‐Moghadasi, Mohammad; Ali Sadeghzadeh, Ramazan; Singh Virdee, Bal
Abstract : Empirical results are presented for a novel hexa‐band coplanar waveguide (CPW)‐fed antenna that consists of three asymmetric fork‐shaped radiating elements incorporating U‐shaped radiators with a slit. Each of the three branched radiators generates triple resonant frequencies within the L, S, C and X bands. U‐shaped elements with a slit contribute toward generating resonant frequencies at lower band of the antenna. The asymmetrical fork‐shaped elements enhance the impedance matching properties of the antenna and reduce its stopband. The proposed antenna design resonates at 1.3, 1.75, 3.35, 4.85, 6.5 and 7.6 GHz that covers the following wireless communications standards: global system for mobile communications (GSM) (880–960 MHz), digital cellular system (DCS) (1.71–1.88 GHz), personal communication system (PCS) (1.85–1.99 GHz), Bluetooth (2.402–2.480 GHz), wireless local area network (2.4/5.2/5.8 GHz), worldwide interoperability for microwave access (2.3–2.4/2.496–2.690/3.3–3.8 GHz), wireless fidelity (2.412–2.4835/4.9–5.9 GHz). A prototype hexa‐band antenna was fabricated and tested. The measured results conform to the simulated ones. The proposed antenna essentially radiates omnidirectionally in both the E and H planes with a peak gain of 5.27 dBi and efficiency of 81.3% at 4.85 GHz. The antenna has dimensions of 35 × 26 mm 2 . The antenna is an excellent candidate for multiband and broadband communication applications.